Pasajes para la memoria el recorrido como estrategia para resignificar y recuperar pasajes culturales en el contexto patrimonial del centro de Bogotá (2023)
In the course of time of heritage scenarios of the historic center of the city of Bogotá, conditions inherent to time, transform the way in which commercial and cultural passages interact, losing relevance in social development and, in turn, appropriation of the population from its immediate context. Through the tour, it is proposed to recover the collective memory, revitalizing these spaces again, reactivating commerce and resignifying the passages, proposing an intervention strategy in the basements of Avenida Jiménez and including El Pasaje Rivas, El Pasaje Hernández and El Pasaje Mercedes Gómez as case studies. Using the route, photography, planimetric survey and historical review, it was possible to identify the characteristics of the passages, defining parameters and criteria to generate an intervention strategy establishing the importance and relevance of its rehabilitation, finally highlighting the events that happened there.